Pengembangan Kompetensi Mahasiswa untuk Analisis Data Statistik dengan Aplikasi Rstudio - Suseno, Pangki (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Digital technology has brought significant changes to education, especially in statistics and data analysis. Now, data processing skills are essential for students across all disciplines. R Studio, a popular open-source software for statistical analysis, can assist with this process. This community service activity consists of a workshop on using R Studio for industrial engineering and computer science students. The workshop aims to enhance understanding of R Studio's basic concepts and practical data analysis skills. Implementation methods include lectures, hands-on practice, and pre- and post-training evaluations. The material covers an introduction to R and R Studio; installation; basic R syntax; data import and manipulation; descriptive statistical analysis; and visualization using ggplot. Results showed that all participants understood the installation process and that 70% could use R Studio for statistical analysis and develop solutions. The final evaluation revealed that the training helped students solve data problems quickly and accurately.